Utility of Tetrahydrobiopterin Pathway in the Assessment of Diabetic Foot Ulcer: Significant and Complex Interrelations - Marwan Al-Nimer; Rawa Ratha; Taha Mahwi (Journal of Diabetes Research)
Objectives. Tetrahydrobiopterin (BH4) pathway that included generation of neopterin (Neop), biopterin (Biop), and nitric oxide (NO) is altered in type 2 diabetes (T2D). The aim of this study was to assess the biomarkers of BH4 pathway in noninfected DFUs and to relate these levels to the variables of diabetes as well as to the hematological indices. Methods. We performed a cross-sectional investigating study in a Kurdish people including 30 healthy subjects (group I), 66 T2D patients (group II), and 57 DFUs patients (group III). Hematological indices including red cell distribution width (RDW), mean platelet volume (MPV), and platelet distribution width (PDW) were determined by Coulter hematological analysis. Serum BH4 markers including NO, Neop, and Biop were determined by using an enzyme-linked immunosorbent assay (ELISA) technology. The relationship between BH4 markers with glycemic and hematological indices was assessed by Spearman’s correlation and multivariable regression analysis. Results. Neop was significantly increased while PDW was significantly decreased in group III compared with group II patients. Nitric oxide was found to be inversely correlated with age (r=−0.382), duration of diabetes (r=−0.264), mean arterial blood pressure (r=−0.532), body mass index (r=−0.321), RDW (r=−0.322), and PDW (r=−0.284) in group III patients. Circulating Neop and Biop significantly correlated with RDW and erythrocyte sedimentation rate. Multivariable regression analysis revealed that serum Neop predicted the DFUs in 92.5% of group III patients. Conclusion. Tetrahydrobiopterin biomarkers are predictors of DFUs and the significant correlation of neopterin with red distribution width and erythrocyte sedimentation rate indicating the role of neopterin in the vascular and inflammation concerns of noninfected DFUs.